Region-specific Epithelial Cell Dynamics During Branching Morphogenesis - Hsu, Jeff C. (2013)
BACKGROUND: Epithelial cells of developing embryonic organs, such as salivary glands, can display substantial motility during branching morphogenesis. Their dynamic movements and molecules involved in their migration are not fully characterized. RESULTS: We generated transgenic mice expressing photo-convertible KikGR and tracked the movements of individual cells highlighted by red fluorescence in different regions of developing salivary glands. Motility was highest for outer bud epithelial cells adjacent to the basement membrane, lower in inner bud cells, and lowest in duct cells. The highly motile outer cells contacting the basement membrane were pleomorphic, whereas inner cells were rounded. Peripheral cell motility was disrupted by antibodies inhibiting α6+β1 integrins and the non-muscle myosin II inhibitor blebbistatin. Inner bud cell migration was unaffected by these inhibitors, but their rate of migration was stimulated by inhibiting E-cadherin. CONCLUSIONS: Cell motility in developing salivary glands was highest in cells in contact with the basement membrane. The basement membrane-associated motility of these outer bud cells depended on integrins and myosin II, but not E-cadherin. In contrast, motility of inner bud cells was restrained by E-cadherin. These findings identify the importance of integrin-dependent basement membrane association for the morphology, tissue organization, and lateral motility of morphogenetic epithelial cells.